THE PROCESS OF FORMATION AND ASSESSMENT OF THE LEVEL OF CONSUMER LOYALTY ORGANIC PRODUCTS - SHARKO, Vitalii; ANDRUSENKO, Nadia; VASYLYSHYNA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The vast majority of domestic companies aim to retain customers. The question of the peculiarities of measuring and assessing the level of consumer loyalty to organic products remains insufficiently studied. Therefore, scientific and practical interest in this problem necessitates the development of a methodological platform for this process. The choice of evaluation criteria and interpretation of the obtained data are characterized by a certain complexity. Therefore, it is necessary to evaluate the retrospective experience of consumer interaction with the enterprise and its possible behavior in the future. Also, we should take into account the dynamic and nonlinear formation of loyalty, its propensity to be influenced by many factors that are related to both the characteristics of the consumer and the dynamic external environment. The aim of the study is to develop a combined methodology for assessing the level of consumer loyalty, which would provide complete and reliable data and would be suitable for practical activities. Theoretical and practical aspects of research of loyalty of consumers of organic products under modern conditions of strengthening of competition and globalization of the food market are investigated in the work. A combined method of assessing the level of consumer loyalty is presented, which would provide complete and reliable data and would be suitable for the practical activities of enterprises. The results of scientific research of this article will allow companies producing organic products to adjust their actions towards building long-term mutually beneficial relationships with consumers, and will be the key to achieving other goals directly or indirectly related to high customer loyalty.